THE CLINICAL SIGNIFICANCE OF THE DAILY MONITORING OF HOLTER ECG IN CHRONIC GLOMERULONEPHRITIS AT THE PREDIALYSIS STAGE OF THE DISEASE - I. T. Murkamilov; I. S. Sabirov; V. V. Fomin; Zh. A. Murkamilova; A. I. Sabirova; K. A. Aitbaev; B. Zh. Imanov; N. A. Redzhapova; F. A. Yusupov (SINAPS LLC, 2019)
This article presents the results of our own research: comprehensive clinical and laboratory examinations, including data from the daily Holter monitoring of the electrocardiogram (DMEKG) in 169 patients with chronic glomerulonephritis at the predialysis stage of the disease. According to the DMEKG, 60.3% of the persons examined by us had episodes of supraventricular group extrasystoles, and ventricular group extrasystoles in 28.9%. In addition, 11.2% of patients had atrial ventricular blockade (incomplete / partial), 8.8% had atrial fibrillation and painless ischemia in an amount of from 1 to 3 episodes per day in 14.7%. Depending on the average heart rate (HR) according to the DMEKG, patients with chronic glomerulonephritis were divided into two subgroups. Subgroup "A" included 38 patients with heart rate less than or equal to 70 beats / min, in subgroup "B" - 131 patients with a heart rate of more than 70 beats / min. With equal values of uric acid, total cholesterol cholesterol, HDL cholesterolcholesterol, TG, plasma creatinine and blood fibrinogen in subgroup "B" there was a statistically significant increase in LDL cholesterol concentration(3.58 (2.74; 5.54) mmol / l vs. 2, 82 (2.30; 3.86) mmol / l; p <0.05) and a decrease in the calculated GFR (70.4 (48.8; 96.3) ml / min vs. 85.7 (31.5; 103,1) ml / min; p <0.05) compared with subgroup "A". In the subgroup "B" a tendency was observed to increase the degree of daily excretion of protein with urine. The data obtained confirm the fact that the conduct of the DMEKG with the analysis of heart rate is of significant clinical importance for the diagnosis of cardiovascular disorders and the p revention of cardiovascular complications in chronic glomerulonephritis at the predialysis stage of the disease.